Biocompatibility of Bioactive Sealers Bio-C Sealer vs MTA Repair HP in Human Fibroblasts - Méndez-González, Verónica M.; Martínez-López, Joselyn; Pozos-Guillén, Amaury; González-Amaro, Ana M.; Gutiérrez-Sánchez, Mariana; Escobar-García, Diana M. (Odovtos - International Journal of Dental Sciences, 2024)
Bioactive cements based on tricalcium silicate have been introducedto the market for use in dentistry, with a variety of clinical applications. These cements are in contact with vital tissues such as dental pulp or periodontium in cases of unintentional extrusion; thus, it is important to know the genotoxicity and cytoxicity of these materials. The objective of this study was to evaluate the cytotoxicity and genotoxicity of bioactive sealers, Bio-C® Sealer and MTA Repair HP®, in human fibroblasts. Discs of bioactive sealers Bio-C® Sealer, and MTA Repair HP®, were prepared and set for 24h under sterile conditions. The discs were placed in culture medium at 2.5mg/mL inside a SRT6D roller mixer (Stuart, UK) at 60rpm for 24h. The eluates obtained were incubated for 24h with previously activated and cultured ATCC cell line fibroblasts at 80% confluence. The cytotoxicity was evaluated by Alamar Blue® and LIVE/DEAD assays, as well as the analysis of the Tunel and Mitotracker assays to evaluate genotoxicity using the confocal laser-scanning microscope. In the Alamar Blue® assay, the Bio-C® Sealer presented a cell proliferation of 87%, while the MTA Repair HP® Sealer was 72%. A statistically significant difference was found between the MTA Repair HP® Sealant and the negative control (p=<0.001). Regarding the genotoxicity tests, in the Tunel assay, both materials stain the nucleus of the fibroblast cells exposed to the eluates, while in the Mitotracker assay, the MTA Repair HP® Sealer showed greater mitochondrial function than the Bio-C® Sealer. Calcium silicate-based sealers, Bio-C® Sealer and MTA Repair HP®, are not cytotoxic and have low genotoxicity.